Building Dams in Permafrost Regions (Stroitelstvo Plotiny v Raione Vechnoi Merzlety) - Semenov,N. G. (1974)
By observations, the author has confirmed the possibility of erecting dams in permafrost regions on loose soils containing much ice and he has shown that the complete freezing of a dam's body with the aid of flowing cold air through (according to a special system built into the dam) occurs quite intensively. He details the procedures involved in planning and building the dam in a permafrost region. Draft trans. of Gidrotekhnicheskoe Stroitelstvo (USSR) n9 p14-15 1967.